Effectiveness of Archives Systems in Administrative Governance at the Maccini Sombala Village Head Office, Makassar City - Jamaluddin, Jamaluddin; Nurfadila, Nurfadila; Isgunandar, Isgunandar (Pinisi Journal of Education and Management, 2023)
Good records management plays an important role in organizational effectiveness, especially in administrative governance, namely supporting the availability of information effectively and efficiently, as planning material, policy-making material, control function, decision-making, evaluation, and accountability material. In reality, there are still many agencies that pay little attention to archive management which deviates from archival regulations. This research aims to determine the archival system in administrative governance, supporting factors, and inhibiting factors in the archival system in office administrative governance at the Maccini Sombala Village Head Office, Makassar City. This research is a qualitative descriptive research to explore all the information and information obtained in detail during the research process. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques used are data collection, reduction, data presentation, and verification. The test results show that the archive system in administrative management at the Maccini Sombala Village Head Office, Makassar City, which includes dynamic archive management, has not been implemented effectively. This is due to the archive storage process being not optimal, namely using only one filing cabinet for all types of archives so that the archives can get scattered. The lack of attention from archival staff regarding archive supervision also means that archives are still piled up on office desks. Supporting factors for fast archive services, so that incoming archives can be processed immediately. The inhibiting factor for the archive system is limited facilities and infrastructure for managing and maintaining archives